ACG Clinical Guideline: Upper Gastrointestinal and Ulcer Bleeding - Laine, Loren; Barkun, Alan N.; Saltzman, John R.; Martel, Myriam; Leontiadis, Grigorios I. (The American journal of gastroenterology, 2021)
We performed systematic reviews addressing predefined clinical questions to develop recommendations with the GRADE approach regarding management of patients with overt upper gastrointestinal bleeding. We suggest risk assessment in the emergency department to identify very-low-risk patients (e.g., Glasgow-Blatchford score = 0–1) who may be discharged with outpatient follow-up. For patients hospitalized with upper gastrointestinal bleeding, we suggest red blood cell transfusion at a threshold of 7 g/dL. Erythromycin infusion is suggested before endoscopy, and endoscopy is suggested within 24 hours after presentation. Endoscopic therapy is recommended for ulcers with active spurting or oozing and for nonbleeding visible vessels. Endoscopic therapy with bipolar electrocoagulation, heater probe, and absolute ethanol injection is recommended, and low- to very-low-quality evidence also supports clips, argon plasma coagulation, and soft monopolar electrocoagulation; hemostatic powder spray TC-325 is suggested for actively bleeding ulcers and over-the-scope clips for recurrent ulcer bleeding after previous successful hemostasis. After endoscopic hemostasis, high-dose proton pump inhibitor therapy is recommended continuously or intermittently for 3 days, followed by twice-daily oral proton pump inhibitor for the first 2 weeks of therapy after endoscopy. Repeat endoscopy is suggested for recurrent bleeding, and if endoscopic therapy fails, transcatheter embolization is suggested.